Evaluation of the Tobbstop Mobile App for Smoking Cessation: Cluster Randomized Controlled Clinical Trial - Pallejà-Millán, Meritxell; Rey-Reñones, Cristina; Barrera Uriarte, Maria Luisa; Granado-Font, Esther; Basora, Josep; Flores-Mateo, Gemma; Duch, Jordi (JMIR Publications, 2020)
BackgroundMobile apps provide an accessible way to test new health-related methodologies. Tobacco is still the primary preventable cause of death in industrialized countries, constituting an important public health issue. New technologies provide novel opportunities that are effective in the cessation of smoking tobacco. ObjectiveThis paper aims to evaluate the efficacy and usage of a mobile app for assisting adult smokers to quit smoking. MethodsWe conducted a cluster randomized clinical trial. We included smokers older than 18 years who were motivated to stop smoking and used a mobile phone compatible with our mobile app. We carried out follow-up visits at 15, 30, and 45 days, and at 2, 3, 6, and 12 months. Participants of the intervention group had access to the Tobbstop mobile app designed by the research team. The primary outcomes were continuous smoking abstinence at 3 and 12 months. ResultsA total of 773 participants were included in the trial, of which 602 (77.9%) began the study on their D-Day. Of participants in the intervention group, 34.15% (97/284) did not use the app. The continuous abstention level was significantly larger in the intervention group participants who used the app than in those who did not use the app at both 3 months (72/187, 38.5% vs 13/97, 13.4%; P<.001) and 12 months (39/187, 20.9% vs 8/97, 8.25%; P=.01). Participants in the intervention group who used the app regularly and correctly had a higher probability of not being smokers at 12 months (OR 7.20, 95% CI 2.14-24.20; P=.001) than the participants of the CG. ConclusionsRegular use of an app for smoking cessation is effective in comparison with standard clinical practice. Trial RegistrationClinicaltrials.gov NCT01734421; https://clinicaltrials.gov/ct2/show/NCT01734421